GERMADAN RAWA PENING: TINDAKAN BERSAMA DALAM PENGELOLAAN COMMON POOL RESOURCES (Germadan Rawa Pening: Collective action in managing common pool resources) - S. Agung Sri Raharjo; Faiqotul Falah; S. Andy Cahyono (Center for Implementation of Standards for Environmental and Forestry Instruments Solo, 2019)
ABSTRACTGermadan is one form of lake management policy implemented through the establishment of institutions involving many stakeholders. The institutional management of the Rawa Pening Lake is a collective action to the preservation of the Rawa Pening Lake. This study aimed to evaluate the implementation of Germadan in the perspective of the theory of collective action. The research used a qualitative approach. Data collection through in-depth interviews, observation, and literature study. The descriptive analysis was carried out to describe the implementation and to identify the successes and failures of Germadan. Based the analysis, it can be concluded that as a collective action, Germadan has failed. This failure is due to imperfection of participation in planning and implementation of the program, and the lack of enforcement of agreed rules and lack of incentives for both economic and social incentives in their implementation.Keywords: Germadan; Rawa Pening; collective action; stakeholders ABSTRAKGermadan merupakan salah satu bentuk kebijakan pengelolaan danau yang dilaksanakan melalui pembentukan kelembagaan yang melibatkan banyak pemangku kepentingan. Kelembagaan pengelolaan Danau Rawa Pening merupakan tindakan bersama untuk kelestarian Danau Rawa Pening. Penelitian ini bertujuan mengevaluasi pelaksanaan Germadan dalam perspektif teori collective action. Penelitian menggunakan pendekatan kualitatif. Pengumpulan data melalui wawancara mendalam, observasi, dan studi pustaka. Analisis secara deskriptif dilakukan untuk menggambarkan pelaksanaan Germadan dan mengetahui keberhasilan maupun kegagalan collective action dalam Germadan. Berdasarkan analisis dapat disimpulkan bahwa sebagai sebuah tindakan bersama, Germadan telah gagal. Kegagalan ini disebabkan oleh partisipasi dalam penyusunan perencanaan dan pelaksanaan program tidak sempurna, dan tidak adanya upaya penegakan aturan yang telah disepakati serta kurangnya insentif baik insentif ekonomi maupun sosial dalam pelaksanaannya.Kata kunci: Germadan; Rawa Pening; collective action; pemangku kepentingan